Improving fleet efficiency to maximise economic yield in a Western Australian prawn fishery. (December 2017) - Hesp, Sybrand; Caputi, Nick; Penn, Jim; Kangas, Mervi; Sporer, Errol; Hogan, Brett; Clement, James
Abstract: The Shark Bay trawl fishery is Western Australia's most valuable prawn fishery (worth AUD$25 million in 2014). The 18-vessel fleet targets western king prawns ( Penaeus latisulcatus ), brown tiger prawns ( P. esculentus ) and also retains saucer scallops ( Ylistrum balloti ) and blue swimmer crabs ( Portunus armatus ). Increased fuel prices, falling prawn prices and lower catches of other species, following extreme environmental events, have impacted fishery profits. A biomass dynamics model with an economic component indicated that total revenue levels start to decline when annual effort increases beyond ~ 200 fishing days per boat. Annual effort required to achieve MEY, when based solely on prawn fishing, is 115–150 days per boat after accounting for fixed and variable fishing costs and annual fishing efficiency increases of 1–2%. From 2007–2014, the adjusted effort was 188–192 days per boat. Fishing occurred between March and November during 7–8 fishing periods, separated by 5–8 day (low catchability) moon closure periods. An empirical daily profit assessment (2007–2015), accounting for recruitment variation, daily prawn size compositions, monthly market prices for different prawn species and sizes, and daily fishing costs, showed vessels made profits on ~ 115–160 days and losses on ~ 15–55 days per year, when fishing occurred near the full moon. The fishery benefitted in 2013–2015 by starting later in the year and better targeting within-season effort. This management strategy within the effort-control framework, which improved profitability, maintained higher spawning stocks and reduced ecosystem fishing impacts, has wider application in prawn fishery management. Highlights: Model-based assessment provides useful estimates of effort required to achieve MEY. Complementary daily profit assessment allows for better targeting of effort to optimize catch value. Profitability can be improved by increasing moon closure periods and delaying the start of the fishing season. Methods likely to have wider application to other prawn fisheries.